2014
DOI: 10.1016/j.jfineco.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Elections, political competition and bank failure

Abstract: We model and predict that politicians have incentives to delay bank failure in election years and that this incentive is exacerbated if the election is close. Our empirical application using the US data supports these predictions. At the bank level, we show that bank failure in an election year is four times less likely to occur if the election was among the most competitive (top quartile). At the state level, bank failure is about 1.8 times less likely to occur in an election year. A three point swing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…A positive relationship is expected between GDP growth and business opportunities for banks and thus, the scope and boundaries of banks (Albertazzi & Gambacorta, 2009; Bernanke, Gertler, & Gilchrist, 1999; Goddard et al, 2011). We have included a dummy variable for the years 2007 and 2008, which indicate the beginning of the most recent economic crisis ( Crisis ; Liu & Ngo, 2014; Spokeviciute, Keasey, & Vallascas, 2019). Table 2 shows the descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
“…A positive relationship is expected between GDP growth and business opportunities for banks and thus, the scope and boundaries of banks (Albertazzi & Gambacorta, 2009; Bernanke, Gertler, & Gilchrist, 1999; Goddard et al, 2011). We have included a dummy variable for the years 2007 and 2008, which indicate the beginning of the most recent economic crisis ( Crisis ; Liu & Ngo, 2014; Spokeviciute, Keasey, & Vallascas, 2019). Table 2 shows the descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
“…This paper joins several recent studies that examine the economic impact of political uncertainty using gubernatorial election data. Liu, Phong, and Ngo (2014) document that bank failure is lower during gubernatorial elections in the United States. Gao and Qi (2013) find that municipal bond yields increase, and Jens (2016) shows that corporate investment is lower during such times.…”
Section: Introductionmentioning
confidence: 99%
“…Several finance studies have documented that politically connected banks are more likely to receive support from the government in times of economic distress (Blau, Brough, &Thomas, 2013); thus these banks are more likely to engage in risk taking activities (Kostovesky, 2015). Bank failure is about 45% less likely in the year leading up to an election, perhaps to avoid the political costs associated with failure (Liu & Ngo, 2014). Moreover, Chaney et al (2011) have found that politically connected firms with poor accounting information do not suffer higher cost of debt, consistent with the argument that political connections mitigate the costs of poor accounting information.…”
Section: Introductionmentioning
confidence: 64%